Los verbos frasales como elementos del marco locucional - Martínez López, Juan A.; Reyes Tejedor, Mariano (Pontificia Universidad Católica del Perú, 2024)
The present study takes as its starting point the exclusion that phrasal verbs traditionally have experienced in the field of phraseological studies, and more specifically, those carried out in the sphere of locutions. In order to determine if the mentioned exclusion has been correct, we have carried out a detailed analysis of a corpus of 50 phrasal verbs, in light of the academic debate that during the last decades has been establishing the main defining criteria of the phrases. The criteria mentioned have been two of a formal nature, such as multiverbality and fixation, and one semantic, the idiomaticity of the whole structure. After this analysis, we have been able to verify that, with certain formal peculiarities typical of these verb+preposition as the propositional reaction and its role as an attachment to the verb, phrasal verbs fully meet the defining criteria.

El presente estudio toma como punto de partida la exclusión que tradicionalmente han experimentado los verbos frasales en el ámbito de los estudios fraseológicos y, más concretamente, de aquellos realizados en la esfera de las locuciones. Al objeto de determinar si dicha exclusión ha sido acertada, hemos realizado un análisis pormenorizado de un corpus de 50 verbos frasales, a la luz del debate académico que durante las últimas décadas ha ido asentando los principales criterios definitorios de las locuciones. Dichos criterios han sido dos de carácter formal, como son la pluriverbalidad y la fijación, y uno semántico, la idiomaticidad del conjunto. Tras dicho análisis, hemos podido constatar que, con ciertas peculiaridades formales propias de estas estructuras de verbo+preposición como es la rección preposicional y su papel como anexo del verbo, los verbos frasales cumplen plenamente los criterios definitorios.
Phrasal verbs as elements of the locutionary frame
Keywords: Phrasal verbs; Structural fixation; Idiomaticity; Locution; Pluriverbality; Verbos frasales; Fijación estructural; Idiomaticidad; Locución; Pluriverbalidad; https://purl.org/pe-repo/ocde/ford#6.02.06